2013
DOI: 10.1111/pce.12183
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizas with Paxillus involutus enhance cadmium uptake and tolerance in Populus × canescens

Abstract: ABSTRACTuptake, transport and detoxification processes were increased in EMs compared to non-mycorrhizal roots. Higher CO2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to non-mycorrhizal poplars despite higher Cd 2+ accumulation. These results indicate that mycorrhizas increase Cd 2+ uptake, probably by an enlarged root volume and overexpression of genes involved in Cd 2+ uptake and transport, and concurrently enhance Po. × canescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
101
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 98 publications
(249 reference statements)
7
101
0
1
Order By: Relevance
“…To date, few studies have reported on the effects of mycorrhizal fungi on the acclimatization of microplants of forest trees to ex vitro conditions. A positive effect of in vitro ECM inoculation on poplar growth was previously reported for Populus tremula L. 9 Populus tremuloides Mich (Hampp et al 1996;Loewe et al 2000) and for P. 9 canescens (Gafur et al 2004;Li et al 2012;Ma et al 2014). Inoculation of microplants ex vitro with mycorrhizal fungi has been shown to improve poplar survival rate, health status, and growth post-acclimatization (Langer et al 2008).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…To date, few studies have reported on the effects of mycorrhizal fungi on the acclimatization of microplants of forest trees to ex vitro conditions. A positive effect of in vitro ECM inoculation on poplar growth was previously reported for Populus tremula L. 9 Populus tremuloides Mich (Hampp et al 1996;Loewe et al 2000) and for P. 9 canescens (Gafur et al 2004;Li et al 2012;Ma et al 2014). Inoculation of microplants ex vitro with mycorrhizal fungi has been shown to improve poplar survival rate, health status, and growth post-acclimatization (Langer et al 2008).…”
Section: Introductionmentioning
confidence: 74%
“…Both, ectomycorrhizal (ECM) and arbuscular mycorrhizal (AM) associations may play an important role in establishment of vegetation in highly polluted soils (Turnau et al 2006). The ability to accumulate and detoxify heavy metals show ECM fungi (Turnau et al 1996;Rudawska and Leski 2005;Ott et al 2002;Luo et al 2014;Ma et al 2014) and AM fungi (Joner et al 2000;Hildebrandt et al 2007;Bissonnette et al 2010;Bothe et al 2010;Cicatelli et al 2014). Mycorrhizal fungi can also enhance the host plant tolerance by influence on its defence genes ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is well documented in wooden plants that go into the mutualistic mycorrhizal symbiosis and produce ectomycorrizal roots which preserve, store and exchange mineral salts and water [9]. It has been shown that this type of plant association with fungi significantly enhance their tolerance to toxic concentration of heavy metals in soil [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%